Western Balkans Regular Economic Report No. 15, Spring 2019 : Reform Momentum Needed - World Bank Group (World Bank, Washington, DC, 2019)
The Western Balkans economies are projected to continue to expand in 2019–20, but this stable outlook is vulnerable to risks. In 2018 economic growth in the Western Balkans reached 3.8 percent, supported by increased public spending, and in Albania and North Macedonia also by a rise in net exports. Growth is projected to average 3.7 percent for 2019–20, faster than the EU and similar to the average for Central and Eastern Europe (CEE). Growth will differ by country, accelerating in Bosnia and Herzegovina, Kosovo, and North Macedonia while decelerating in Albania, Montenegro, and Serbia. Factors common to all countries are the recent fiscal stimuli and favorable external conditions that pushed growth in 2018, beyond its potential in some of them. The waning effects of these factors challenges the medium-term growth outlook in the region. Moreover, there is growing public discontent in several countries which could lead to higher political uncertainty and a slower pace of structural reforms. In North Macedonia, by contrast, the resolution in early 2019 of the decades-long dispute with Greece over the country’s name is an opportunity to advance reforms, accelerate EU accession, and become more integrated in global markets. Western Balkan countries are also confronted with growing external risks from slower-than projected growth in the EU, geopolitical and trade disputes, and a possible tightening of financing conditions in international capital markets. Against this backdrop, there is anopportunity to advance reforms to mitigate risks and the demands for greater economic opportunities. This report features a special focus section on human capital development. The region has achieved notable progress in expanding access to basic education and health and setting up social protection systems to protect the vulnerable. This Focus Section explores how Western Balkan societies can be better prepared to take advantage of the opportunities offered by rapid technological changes, mitigate risks, and create dynamic growing economies where young people can thrive and realize their aspirations. Unaddressed, the region’s human capital challenges will severely limit the region’s prospects for growth and poverty reduction. For instance, too little investment in early childhood development translates into poor performance in primary and secondaryeducation in some countries. In school, students in some countries do not acquire the skills they need to function effectively as labor markets become ever more competitive. Poor quality technical and university education makes the transition from school to work difficult; many graduates who suffer years of unemployment cannot build work experience. Social assistance programs also do not give vulnerable households the support they need to prepare them for the labor market. Inefficient health systems are unable to address the rise of noncommunicable diseases, and individual out-of-pocket spending on health is high. In general, countries in the region must act boldly to build human capital.